Effect of surfactant lengths on gas-liquid oxygen mass transfer from a single rising bubble. (16th January 2022) - Lebrun, Gaëlle; Benaissa, Sanae; Le Men, Claude; Pimienta, Véronique; Hébrard, Gilles; Dietrich, Nicolas
Graphical abstract: Highlights: Study of the surface contamination by surfactants in function of their nature. kL measured by PLIF-I for a large panel of surfactants and concentrations. Increasing the hydrophilic part of nonionic surfactants doesn't impact the kL . Increasing the length of cationic surfactants leads to a decrease of kL . Abstract: This work is an experimental investigation of the effect of the nature of surfactants on oxygen mass transfer. The study focuses on three cationic surfactants with different hydrophobic chain lengths, and four nonionic surfactants with different hydrophilic chain lengths. Equilibrium adsorption isotherms are calculated for each surfactant from experimental values of surface tension in static conditions. Surfactant solutions at concentrations between 2.5 × 10 -8 and 5 × 10 -3 mol/L were prepared and oxygen transfer from millimetric air bubbles (between 0.82 and 1.08 mm) was measured by Planar Laser Induced Fluorescence with Inhibition (PLIF-I). When the bulk concentration of surfactant was increased, results showed a sharp decrease of bubble velocity, in the range of 283–75 mm/s, and of liquid-side mass transfer coefficient, in the range of 5.6 × 10 -4 –0.4 × 10 -4 m/s. This effect was observed for all surfactants studied. However, the length of the hydrophilic chain did not appear to affect the hydrodynamics of the rising bubble or the oxygen transfer at the same bulk concentration. Furthermore, for the same bulk concentration, increasing the hydrophobic chain length had an impact on the velocity and the mass transfer coefficient of oxygen. Finally, the Sherwood number was calculated in each medium and compared with classical correlations for gas–liquid mass transfer prediction. Those correlations seemed to reach a limit for a very concentrated medium.